Influence of the temperature and humidity on the dairy production of Barbalha, Ceará, Brazil - Lima, Mirelle Tainá; FEITOSA, JOSÉ VALMIR; OLIVEIRA, CARLOS WAGNER; LIMA DA COSTA, ANTÔNIO NÉLSON (Pubvet, 2020)
This work aimed to estimate the influence of climatic factors over the cattle milk production in the municipality of Barbalha, ceará, through temperature and relative humidity data to get the temperature and humidity index - hti. Firstly, a thirty-year (1986 to 2016) meteorological data survey was carried out for the municipality of Barbalha-CE, obtained from the automatic meteorological station of the National Institute of Meteorology (INMET), located at the Embrapa Experimental Station in the same city. About the data of dry bulb temperature and relative air humidity three collections were done daily (at 0:00, 12:00 and 18:00 h). The HTI of Barbalha, for dairy cattle, finds in the mostly times a level of HTI that requires attention. Thus, it’s possible to get better the production improving the elements related to Temperature and Humidity. About the studied hours, the 21:00 p.m. represented the best time for thermal comfort, followed by 9:00 a.m. and 3:00 p.m. presented the worst results of thermal comfort. Thus, the producer must pay attention to the favorable time for the cattle management, that will improve the animal welfare and, consequently, milk production.
Keywords: dairy cattle; semiarid climate; welfare